Strategic Management in Corporate Transformation for Addressing Industry Uncertainty : An Annual Report–Based Study of Electricity Companies in Indonesia - Dr. Rio Afrianda (Prodi Magister Manajemen Universitas Dirgantara Marsekal Suryadarma, 2026)
The This study examines the role of strategic management in corporate strategy transformation within Indonesia’s electricity companies in responding to industry uncertainty. Using annual reports as the primary data source, this research applies qualitative thematic analysis to identify strategic patterns related to transformation, digitalization, and corporate governance. The findings reveal that strategic management serves as a fundamental guiding framework that enables firms to design and implement corporate strategy transformation in a structured and consistent manner. Corporate strategy transformation functions as a key mediating mechanism that translates strategic planning into organizational adaptability and resilience. Furthermore, the study finds that digitalization and good corporate governance act as reinforcing factors that strengthen the effectiveness of strategic transformation by improving decision-making quality, operational efficiency, accountability, and stakeholder trust. Collectively, strategic management, corporate strategy transformation, digitalization, and corporate governance form an integrated strategic system that enhances organizational resilience amid regulatory, technological, and market uncertainty. This study contributes to the strategic management literature by emphasizing the importance of transformation mechanisms and enabling capabilities in sustaining performance within highly regulated and uncertain industries, particularly the electricity sector in emerging economies.